ANALISIS KUAT TEKAN BETON SELF COMPACTING CONCRETE (SCC) YANG MENGGUNAKAN LIMBAH PECAHAN BETON SEBAGAI AGREGAT KASAR: Analysis of Strong Press Concrete (SCC) Using Concrete Solid Waste as a Cough Aggregate - Erwin Syaiful Wagola, Eddy Agus Muharyanto & Muhammad Tharik Kemal (Uniqbu Journal of Exact Sciences, 2020)
The aggregate usage of nature that continually taken or used for the manufacture of concrete mix for civil building construction work can impact for its availability in nature. By him it was one of the alternatives to reduce the intensity of natural aggregate consumption is by utilizing waste concrete shards as fillers in the concrete mix. Self Compacting Concrete (SCC) is very fresh concrete and easy flowing because plastis weight itself fills the whole mold due to the concrete properties to condense on its own, without the help of the vibrator to compaction. Compressive strength of concrete calculated based on the formula, f'c = P/A. Research done with the experimental method, where compressive strength testing done when the concrete was 3, 7, and 28 days. Waste fractions plus concrete into concrete mix SCC with two variations, where variations of the one using 100% of waste fractions of concrete aggregate in lieu of coarse concrete mixtures in SCC, two variations using 50% of waste fractions of concrete and 50% rock burst in the concrete mix SCC. Each variation uses 3 cylindrical test objects with a diameter of 15 cm and a height of 30 cm for 3, 7, and 28 days. The research results show compressive strength of concrete median age 3 days for a variety of one and two respectively 12,88 Mpa and 14,42 Mpa, and at the age of 7 days of compressive strength of concrete average increased to 18,65 Mpa and 20,57 Mpa, and at the age of 28 days and a powerful compressive strength of concrete median to two variations of usage of waste fractions concrete increased by 28.07 Mpa and 30,77 Mpa.